2020
DOI: 10.1037/bul0000219
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence predicts academic performance: A meta-analysis.

Abstract: This meta-analysis shows that emotional intelligence has a small to moderate association with academic performance, such that students with higher emotional intelligence tend to gain higher grades and achievement test scores. The association is stronger for skill-based emotional intelligence tasks than rating scales of emotional intelligence. It is strongest for skill-based tasks measuring understanding emotions and managing emotions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
396
3
25

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 501 publications
(456 citation statements)
references
References 216 publications
(269 reference statements)
32
396
3
25
Order By: Relevance
“…Further, and in partial support of our H3, the results indicated that participants high in emotional intelligence were more likely to use cognitive reappraisal during attempts to regulate their emotions. This finding is consistent with a large body of literature noting emotional intelligence supports the implementation of adaptive coping responses (MacCann et al, 2011(MacCann et al, , 2020. Interestingly, our results demonstrated that levels of emotional intelligence were not associated with the use of suppression-focused strategies during emotion modulation efforts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Further, and in partial support of our H3, the results indicated that participants high in emotional intelligence were more likely to use cognitive reappraisal during attempts to regulate their emotions. This finding is consistent with a large body of literature noting emotional intelligence supports the implementation of adaptive coping responses (MacCann et al, 2011(MacCann et al, , 2020. Interestingly, our results demonstrated that levels of emotional intelligence were not associated with the use of suppression-focused strategies during emotion modulation efforts.…”
Section: Discussionsupporting
confidence: 92%
“…As such, it is predicted that the use of cognitive reappraisal will be positively associated with resilience. H3: Emotional intelligence has been identified as an individual difference variable that supports adaptive emotional information processing and influences attempts to alter emotional experience (MacCann et al, 2020). Specifically, the available literature provides converging evidence that emotional intelligence is associated with the increased use of adaptive emotional regulation strategies and decreased reliance on maladaptive emotion regulation strategies.…”
Section: Hypothesesmentioning
confidence: 99%
“…Future studies should analyse in detail these effects of overlap and collinearity with personality and other aspects to obtain nonbiased findings. Previous review studies (Perera and DiGiacomo, 2013;MacCann et al, 2019) did not assess the impact of different measures of EI on the association with AP, so these findings provide relevant information for future studies. The results showed great heterogeneity within each instrument category, presenting large differences between different studies that used the same instrument to measure EI (Sánchez-Álvarez et al, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Emotional intelligence was assessed with the Emotional Quotient Inventory (EQ-i: YV) [ 31 ] in its Spanish adaptation [ 18 ]. It is a self-report measure that evaluates the EI of children and adolescents between 7 and 18 years old.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Qualter et al [ 17 ], in a longitudinal study with British secondary school students, found that ability EI and trait EI at age 11 predicted AP at age 16. In a recent meta-analysis, MacCann et al, [ 18 ] examined the degree to which students’ EI is associated with academic performance, and they proposed that three mechanisms underlie the EI and AP link: regulating academic emotions, building social relationships at school, and the overlap between academic content and EI.…”
Section: Introductionmentioning
confidence: 99%